Recent development of urinary biomarkers for bladder cancer diagnosis and monitoring - Yuchen Zeng; Anqi Wang; Wei Lv; Qingqing Wang; Shiqi Jiang; Xiaoguang Pan; Fei Wang; Huanming Yang; Lars Bolund; Chunhua Lin; Peng Han; Yonglun Luo (Wiley, 2023)
Abstract Urine‐based liquid biopsy has emerged as a non‐invasive and effective tool for early screening and diagnosis of bladder cancer. This review provides a comprehensive overview of the current urine‐based biomarkers and methods for the detection and monitoring of bladder cancer. We focus on biomarkers including tumour DNAs, proteins, microbiome, tumour RNAs, long non‐coding RNAs, transfer RNA‐derived fragments, messenger RNAs, microRNAs, circular RNAs, exosomes and extrachromosomal circular DNA.